Resilience and Gender as Determinants of Entrepreneurial Intentions among Secondary School Students in Kwara State, Nigeria - Umar Talatu Ibrahim (Indonesian Journal of Educational Counseling, 2020)
The purpose of this study was to investigate resilience and gender as determinants of entrepreneurial intentions among secondary school students in Kwara State, Nigeria. Descriptive research design of ex-post-facto type was used in the study. Five hundred respondents were selected randomly from 5 Local Government Area in Kwara State, Nigeria. The respondents were measured with validated scale and the data obtained was analyzed using the Pearson Product Moment Correlation (PPMC) statistical analysis. Two research hypotheses were formulated and tested at 0.05level of significance. The result showed that there was significant relationship between the resilience and entrepreneurial intentions among secondary school students (r = 0.817; p < 0.05) and there no significant difference in the entrepreneurial intentions of male and female secondary school students (t = 0.71; p > 0.05). In view of these findings, the study recommended that the entrepreneurship training should be made compulsory at all levels of learning from primary schools to the tertiary institutions and curriculum should be tailored towards learning the skills for starting businesses after graduation from school, thus changing the orientation of the students at an early stage towards entrepreneurship.